2013
DOI: 10.1016/j.jped.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and genetic characteristics associated with the severity of acute viral bronchiolitis by respiratory syncytial virus

Abstract: the severity of AVB by RSV is a phenomenon that depends on the varying degrees of interaction among epidemiological, environmental, and genetic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 50 publications
5
52
0
15
Order By: Relevance
“…The considerable number of tests and RSV positive results in infants younger than six months of age and the peak in number and percentage of positive RSV tests in infants aged one month is consistent with existing literature that reports age under six months as a significant risk factor for severe RSV infection (21) and a peak in RSV bronchiolitis at age one month (12) (22). Young infants have been a high priority for vaccination due to the serious complications and subsequent morbidity that can occur following RSV infection in early life (6).…”
Section: Discussionsupporting
confidence: 89%
“…The considerable number of tests and RSV positive results in infants younger than six months of age and the peak in number and percentage of positive RSV tests in infants aged one month is consistent with existing literature that reports age under six months as a significant risk factor for severe RSV infection (21) and a peak in RSV bronchiolitis at age one month (12) (22). Young infants have been a high priority for vaccination due to the serious complications and subsequent morbidity that can occur following RSV infection in early life (6).…”
Section: Discussionsupporting
confidence: 89%
“…Risk factors of RSV positive LRTI are not well defined in our country. In our study, we found risk factors for RSV positivity such as: to be younger than six months, having a low socioeconomic status, shorter duration of breastfeeding and spontaneous [21], assesed the risk factors for RSV bronchiolitis by data synthesis of 60 relevant studies. They found low socioeconomic status and lack of breastfeeding as risk factors which are similar to our study.…”
Section: Discussionmentioning
confidence: 69%
“…A idade média das crianças incluídas no nosso estudo foi de 1,88±1,25 meses. Estudo realizado na Espanha avaliou 229 pacientes internados em UTI pediátrica por BVA e constatou que a idade foi inversamente proporcional ao tempo necessário de suporte ventilatório e de dias de internação em UTI 18,19,20 . Um estudo realizado nos Estados Unidos apontou que de 1,1 milhão de crianças menores de dois anos internadas por VSR em um período de oito anos, a maior porcentagem das internações ocorreu na faixa etária entre três e seis meses 21 .…”
Section: Discussionunclassified